Plan de gestión para el almacenamiento, transporte y evacuación su, cantón Chilla El Oro - Suárez Ramírez, Alvaro David (My University, 2020)
This work deals with the situation in the canton of Chilla, located in the province of El Oro, and describes the management of garbage and its subsequent collection. It also refers to the environmental and legal norms that govern the management of solid waste and with the intervention of the professional part of civil engineering to elaborate and evaluate plans with an investigative focus. The initiative is taken from an exploratory nature in the field, assuming a surveyor role, and making the specific inquiries without forgetting the objectivity of the case, always attached to a scientific method that supports our work, to then process the data obtained through a free software to transform them into statistical graphs and be able to establish alternatives to the management of USW, with the interpretation of the information. The objective of the practical work is to propose alternatives to improve the handling and management of USW in Chilla, through reinforcement of training for the community to make better use of the waste, and to carry out the mission of obtaining another collection truck for the optimization of transport and the elaboration of a study to have its own sanitary landfill, in order to optimize costs and the use of resources.
La presente obra trata sobre la situación que atraviesa el cantón Chilla, ubicado en la provincia de El Oro, y describe el manejo de la basura y su posterior recolección. Además, hace referencia a las normas ambientales y jurídicas que gobiernan el manejo de los residuos sólidos y con la intervención de la parte profesional de la ingeniería civil para elaborar y evaluar planes con un enfoque investigativo. Se toma la iniciativa desde una índole exploratoria en campo, asumiendo un rol encuestador, y haciendo las indagaciones puntuales sin olvidar la objetividad del caso, siempre apegados a un método científico que respalde nuestro trabajo, para luego procesar los datos obtenidos mediante un software libre transformarlos a gráficas estadísticas y poder establecer alternativas al manejo de los RSU, con la interpretación de la información. Se plantea cómo objetivo del trabajo práctico el plantear alternativas para mejorar el manejo y la gestión de los RSU en Chilla, mediante un refuerzo hacia las capacitaciones a la comunidad para un mejor aprovechamiento de los residuos, que se realice la misión de obtener otro camión recolector para la optimización del transporte y la elaboración de un estudio para tener su propio relleno sanitario, a fin de optimizar costos y aprovechamiento de los recursos.
Keywords: RESIDUO; TRATAMIENTO; COMPOST; ECO-EFICIENCIA